‘Off with their heads!’ The imagery of the head in the trilogy of Psalms 108–110 (Part 2) - Sutton, Lodewyk; Human, DJ (Stellenbosch Theological Journal, 2017)
A social-scientific analysis of the word ‘head’ in Psalms 108–110 indicates from another theme (war) and perspective (honour) how the imagery of the head is used to communicate warfare, and to develop and establish the connections between Psalms 108 to 110. This two-part article indicates (in the first article) that the imagery of the head can be considered as part of the imagery of warfare. The value system of honour and shame as expressions of the function and purpose of the warfare imagery is made through a social-scientific analysis of the imagery of the head. The iconography of different ancient Near Eastern contexts is used as extra-textual sources to elucidate the concept of the head as an aspect of warfare imagery, expressing honour and shame. The second article examines and applies the use of the imagery of the head in Psalms 108–110 by integrating the deductions made in this first part. This helps to indicate the development and connections between Psalms 108–110 through utilisation of the imagery of the head.